Enhanced Reflected Group Delay with Optical Tamm State via Graphene-Dielectric Bragg Mirror Configuration - Jiao Tang; Jiao Xu; Hui Zhou; Zhiwei Zheng; Yuxiang Zhou; Rui Weng; Yueying Wei; Yue Liu; Qiwei Liu; Leyong Jiang; Shengyou Qian (Advances in Condensed Matter Physics)
Group delay of the optical pulse reflected from the structure composed of graphene and one dimensional photonic crystal (1D PC) is studied. It is shown that the large negative group delay in this configuration can be realized due to the excitation of the optical Tamm state (OTS) at a graphene-dielectric interface. The reflected group delay can be enlarged negatively and can be switched from positive to negative or vice versa. We show that the conductivity of graphene has a significant influence on reflected group delay, making the graphene-PC structure be a good candidate for dynamic tunable optical delay device in the THz frequencies. Furthermore, the influences of the relaxation time of graphene, the incident angel, and the dispersion characteristics of top layer on group delay are clarified.